Fitler compensating installations in AC traction networks - L. A. German; A. S. Serebryakov; A. A. Maksimova (Вестник Научно-исследовательского института железнодорожного транспорта, 2016)
The article discusses the design solutions to filter compensating installations (FCI), used in traction AC networks. The authors presented summarized calculations for new FCI schemes for the AC traction power system, with determination of circuit solutions for modular FCI in general case of resonant and wideband filters. The scope of FCI schemes for harmonic filtering was evaluated and filtration efficiency of the harmonic components of new FCI schemes was shown. The procedure of calculation of parameters of FCI was determined taking into account the curve of the traction current. A new model of traction load was proposed, reflecting the real harmonic composition of current at the connection point of FCI. The new model of traction load of AC electric rolling stock was applied, characterizing that it become possible to adjust the values of the harmonic components of the traction load, and this brings the curve of the current into the proximity of experimentally measured. A digital model of electric traction system with FCI and model of the EMU was created, allowing to consider various options schemes of FCI (with the decrement of non-sinusoidality of the voltage in traction network) and, if necessary, to adjust the parameters of FCI. The numerical model for simultaneous calculation of the parameters of the system was developed, including system of external power supply (SEPS) with traction substations, FCI, traction network and traction load - electric multiple unit (EMU). Methods to reduce losses in the damping resistor were proposed and justified. The authors presented a comparison of different circuit variants of FCI from viewpoint of reducing the values of the coefficients of harmonic components of the voltage. The optimum variant of FCI is shown.